THE INFLUENCE OF EDUCATIONAL INTERVENTIONS ON DRUG CLASSIFICATION KNOWLEDGE IN WANAR VILLAGE COMMUNITIES, PUCUK SUB-DISTRICT, LAMONGAN DISTRICT - Aditya Sindu Sakti; Jazilah Khikmia Suwandi; Devi Ristian Octavia; Djati Wulan Kusumo; Muhammad Syaiful Amin (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Drugs registered in Indonesia are classified into six drug classes, including over-the-counter (OTC) drugs, cautionary labeling required, prescription drugs, jamu, standardised herbal medicines, and fitofarmaka. Inadequate community knowledge about drug classes has implications for irrational medication. This study aimed to determine the effect of education interventions on community knowledge about the classification of drugs registered in Indonesia. The study was performed using pre-experimental pre-post intervention studies with 55 respondents, and the questionnaire was validated. Factors that affect the level of knowledge of respondents include age, education, and gender (p-value <0.05). Education interventions can increase community knowledge related to the classification of drugs in the community of Wanar Village, Pucuk District, Lamongan Regency. Keywords: Drug Classification, Education, Level of Knowledge